Improving Student Learning Motivation with Peer Tutor Learning Method - Husna, Nida’Ul; Destiani, Puji; Hajron, Kun Hisnan (Prosiding University Research Colloquium, 2021)
The purpose of this study was to increase the effect of using peer tutoring methods as a means of increasing student learning motivation at SD Negeri Gulon 1 in the Covid-19 pandemic era. Based on the results of data analysis in the first cycle with an average of 88.67 before the treatment, while in the second cycle there was an average increase of 100 after the treatment, namely peer tutors. So it can be concluded that using peer tutoring methods can increase student learning motivation.